Whole-genome sequencing of extended spectrum beta lactamases (ESBLs)-producing Klebsiella pneumoniae (kp) isolates from selected hospitals in Malaysia - Adamu, Salawudeen; Ali, Mika’ila Bawa; Mohd Desa, Mohd Nasir; Neoh, Hui-Min; Masri, Siti Norbaya; Joseph, Narcisse; Tengku Jamaluddin, Tengku Zetty Maztura (BioMed Central, 2025)
The resistance of ESBLs-producing Kp to various groups of antibiotics commonly used against infections they caused had become a global threat and required urgent attention. This study assessed the extended spectrum beta-lactamases (ESBLs)-producing Klebsiella pneumoniae isolates in terms of their genomic resistance. An analytical profile index (API) 20E kit was used to confirm a total of 100 clinical isolates of ESBL Klebsiella pneumoniae. The disc diffusion method was used to perform the antimicrobial susceptibility testing (AST), which was followed by the phenotypic detection of ESBLs. Six profiled representative ESBL positive strains were subjected to whole genome sequencing (WGS), multilocus sequence typing (MLST), and phylogenetic tree construction using the sequence data. The study showed that 46(46%) of the 100 isolates were positive for ESBL production and antibiotic susceptibility testing revealed significant resistance to β-lactam antibiotics including monobactam especially ampicillin/sulbactam (40%), cephalosporin groups (cefuroxime, cefotaxime, and ceftriaxone) stood at 51%, 49% and 48% respectively and aztreonam with 49%. The WGS analysis of the representative strains revealed genes encoding resistance to aminoglycoside (StrA4, StrB1, aac(3’)-IIa, aac(6’)-1b, aac(6’)1b-cr-1, aadA16, aph(3’)-VIa and aadA15), trimethoprim (dfrA14 and dfrA27), sulphonamide (sul1_11, sul2_2 and sul2_3), quinolone (QnrB40-1, QnrB10, QnrS2, OqxA and OqxB), tetracycline (tet(A)_4), fosfomycin (fosA3, floR2 and fosA7), macrolid (mph(A)_1), rifampicin (ARR-3), β-lactam (blaCTX-M-15_23, blaCTX-M-55, blaSHV-1_22, blaSHV11_18, blaSHV-11, blaSHV-1_1.1, blaSHV-11_3, blaSHV-11_19, blaTEM-1_1, blaTEM-1_5, blaOXA-51_10, blaOXA-30_1, blaNDM-1, blaLEN6, blaLEN8 and blaLEN21 were detected. The MLST analysis revealed two novel sequence types of representative strains (2 with ST NF* and 12 with ST NF) and four other heterogeneous STs which include ST394, ST985, ST17 and ST11 while the phylogenetic tree of the strains showed closed clonal relationship and lineages with other reference isolates. In conclusion, the study’s results showed a high prevalence of ESBL-producing Kp in the study area, and the representative strains’ genomic contents demonstrated that ESBL-producing Kp in a clinical setting could serve as a reservoir for resistance genes and be the source of genetic transfer to other bacterial species. As a result, ongoing surveillance is required to monitor this endemic situation to prevent an epidemiological outbreak of K. pneumoniae- carrying ESBL.